Price Effects and the Commerce Clause: The Case of State Wine Shipping Laws. Issue 2 (18th April 2013) - Ellig, Jerry; Wiseman, Alan E.
<x xml:space="preserve">Abstract</x> In the wake of Granholm v. Heald, numerous states passed new laws to regulate interstate direct shipment of alcohol that would seem to contradict the spirit, if not the explicit content, of the Commerce Clause. We build on existing scholarship analyzing the empirical impacts of direct shipment barriers to identify how these new laws are likely to influence local market conditions. Drawing on new data that measure posted winery prices and aggregate production levels in 2002 and 2004, we demonstrate how many of these new laws would be expected to effectively diminish, if not altogether remove, the benefits that would normally accrue to consumers from legalized interstate direct shipment of wine. Although empirical analysis of price effects currently plays a very limited role in dormant Commerce Clause cases, our analysis suggests how price data can be used to ascertain whether a state restriction constitutes discrimination against out‐of‐state economic interests.